Membangun Number Sense Anak Usia Dini melalui Eksplorasi Pola Bilangan di TK Annur Deli Serdang - Ade Rahman Matondang; Yulia Tiara Tanjung; Irwansyah Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Number sense is a crucial cognitive foundation for early childhood that significantly influences their mathematical readiness in subsequent levels of education. This quantitative study aims to determine the effect of implementing number pattern exploration methods in building early childhood number sense. The research method used was a quasi-experimental approach with a One-Group Pretest-Posttest Design. The research population consisted of all children in Group B at TK Annur Deli Serdang, with a total sampling of 15 children. Data on children's number sense abilities were collected through structured performance test instruments that measured three main indicators: magnitude awareness, estimation, and understanding of inter-number relationships. The data analysis technique utilized the parametric statistical tool, the Paired Sample T-Test. The descriptive analysis results indicated a significant increase in the children's average number sense score from a pretest score of 42.50 (Starting to Develop category) to 84.15 (Very Well Developed category) in the posttest. The hypothesis testing results showed that the t-value > t-table with a significance level of 0.000 < 0.05. Therefore, it can be concluded that the exploration of number patterns has a significant effect on building early childhood number sense at TK Annur Deli Serdang. Keywords: Number Sense, Number Patterns, Early Childhood, Experimental Research